Inhibitor of apoptosis proteins as therapeutic targets in bladder cancer - Wolf, Philipp (Frontiers in Oncology, 2023)
Evasion from apoptosis is a hallmark of cancer. Inhibitor of apoptosis proteins (IAPs) contribute to this hallmark by suppressing the induction of cell death. IAPs were found to be overexpressed in cancerous tissues and to contribute to therapeutic resistance. The present review focuses on the IAP members cIAP1, cIAP2, XIAP, Survivin and Livin and their importance as potential therapeutic targets in bladder cancer.